(untitled) (American Journal of Islam and Society, 2008)
A revised and expanded version of a dissertation completed at Princeton University in 2000, this book describes the emergence of a distinct Shi`ite communal identity within the larger Islamic community in the period between the First CivilWar (656-61) and the end of the second/eighth century. It draws on the Shi`ite hadith of the Imami (Twelver) tradition in order to construct a rich picture of the developing Shi`ite community, stressing the Shi`ites’ ideas about their relationship to the Imam, to each other, and to non-Shi`ites, particularly the Islamic ummah at large. The work is divided into an introduction and three sections of four chapters each, presenting three major theses. The first four chapters concentrate on the concept of walOEyOE, usually translated as loyalty or allegiance but, as the author suggests, containing a denotation akin to charisma. She argues that from the beginning, Shi`ism’s crucial characteristic was allegiance to Ali ibn Abi Talib during the First CivilWar. Even after his assassination and the end of the war, allegiance to his cause remained fundamental and he remained the primary focus for the Shi`ites’ location of charismatic authority ...